2020
DOI: 10.2105/ajph.2020.305877
|View full text |Cite
|
Sign up to set email alerts
|

Cost of Tuberculosis Therapy Directly Observed on Video for Health Departments and Patients in New York City; San Francisco, California; and Rhode Island (2017–2018)

Abstract: Objectives. To assess costs of video and traditional in-person directly observed therapy (DOT) for tuberculosis (TB) treatment to health departments and patients in New York City, Rhode Island, and San Francisco, California. Methods. We collected health department costs for video DOT (VDOT; live and recorded), and in-person DOT (field- and clinic-based). Time–motion surveys estimated provider time and cost. A separate survey collected patient costs. We used a regression model to estimate cost by DOT type. Re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 17 publications
1
26
0
Order By: Relevance
“…This is the first health economic analysis to evaluate the impact of pandemic-related suspension of DOT on the outcomes of TB management, measured as direct medical cost and DALYs, in a high-income country setting. Prior health economics analyses of VOT were limited to the impact on the cost component, either comparing the costs of VOT and DOT (cost-minimization analysis) (Lam et al, 2019;Beeler et al, 2020) or focusing on the cost of VOT (cost-analysis) (Mirsaeidi et al, 2015). The present study is a full-scale health economic analysis, comparing both the cost and effectiveness (measured as DALYs) of management of active TB with VOT versus SAT during the time of pandemic.…”
Section: Discussionmentioning
confidence: 99%
“…This is the first health economic analysis to evaluate the impact of pandemic-related suspension of DOT on the outcomes of TB management, measured as direct medical cost and DALYs, in a high-income country setting. Prior health economics analyses of VOT were limited to the impact on the cost component, either comparing the costs of VOT and DOT (cost-minimization analysis) (Lam et al, 2019;Beeler et al, 2020) or focusing on the cost of VOT (cost-analysis) (Mirsaeidi et al, 2015). The present study is a full-scale health economic analysis, comparing both the cost and effectiveness (measured as DALYs) of management of active TB with VOT versus SAT during the time of pandemic.…”
Section: Discussionmentioning
confidence: 99%
“…Previous VOT versus DOT comparative studies [ 10 , 11 ] have been based on an overall assessment, including ordinary percentage of compliance. Our mean cumulative function analysis will determine periods with weak compliance.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies reported that in western countries, A-VOT has better patient compliance, cost utility, and acceptability than DOT [ 10 - 13 ]. However, these studies assessed A-VOT according to the number of observations of clinic-based and comprehensive community-based DOT.…”
Section: Introductionmentioning
confidence: 99%
“…For user compliance, the level of use was not high on the patients’ end and low on the observers’ end compared to those in the United States and the United Kingdom [ 15 , 16 ]. Two more system elements would be needed: the audit and notification systems.…”
Section: Discussionmentioning
confidence: 99%
“…However, A-VOT is a platform on which the patient records and uploads a video to the health service, and the health care personnel review the video later [ 14 ]. Two randomized controlled trials in the United Kingdom and the United States reported that both S-VOT and A-VOT could lower health service costs compared to traditional DOT [ 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%